SA Metal Group : could bigger be better? - Metton, Eulalie (SAGE knowledge. Cases., 2016)
SA Metal Group is a growing family business based in Epping, Cape Town. In 2001, the company had expanded to Gauteng, and its operations there were fast exceeding expectations. However, the questions facing SA Metal Group's continuing expansion were multifaceted, given the high standards achieved by SA Metal in the Cape. This text examines SA Metal's transition from medium to large in size in an increasingly competitive national and international market.